Gender-based Violence and the Nordic Paradox:: When things are not what they seem – A short critical reflection (Journal of Comparative Social Work, 2022)
Intimate partner violence against women (IPVAW) is a long-standing and global phenomenon, that is considered, both public health and social problem which seems difficult to tackle (Gracia et al., 2019; Wemrell et al., 2021). Although some research suggests that gender equality plays an important role in reducing IPVAW (Gracia et al., 2019; Wemrell et al., 2021), the so-called Nordic Paradox – a situation where seemingly the most gender equal states, i.e., Nordic countries (including, Norway, Denmark, Sweden and Finland) report the highest numbers of IPVAW – appears to contradict this supposition (Gracia & Merlo, 2016). To date, there is no agreement as to why, and whether, this is the case. In this short paper, I shall review three academic articles that aim to address this contradiction, focusing on their methodologies and limitations. In this essay, firstly, I will discuss how I approached the literature search. Secondly, I will present an overview of IPVAW and the Nordic paradox. Thirdly, I will discuss Gracia and colleagues (2019) and Permanyer and Gomez-Casillas's (2020) analysis, which are based on the same survey (FRA, 2014). Fourthly, I will examine the chosen literature and lastly, I will consider whether, and if so to what extent, high gender equality score and violence against women go hand in hand.